An Institutional Three-Stage Framework: Elevating Academic Writing and Integrity Standards of International Pathway Students - Velliaris, Donna M.; Breen, Paul (Journal of International Students, 2016)
In this paper, the authors explore a holistic three-stage framework currently used by the Eynesbury Institute of Business and Technology (EIBT), focused on academic staff identification and remediation processes for the prevention of (un)intentional student plagiarism. As a pre-university pathway provider—whose student-body is 98% “international”—plagiarism is a prevalent and complex issue that cannot be solved with a single-solution response. The three-stages of identification should be conceived holistically and with each stage being equally important to the assessment of student writing. It is worth noting, however, that the extent to which plagiarism is detected will determine the number of stages involved and the degree the student has transgressed. This framework emphasizes the need for, and importance of, Academic Integrity (AI), literary ownership, assessment transparency, and compatibility with partner institutions.